KARAKTERISTIK PERUBAHAN ORGANISASI SEBAGAI UPAYA PENINGKATAN KINERJA PERUSAHAAN DI INDUSTRI BATIK MASARAN SRAGEN JAWA TENGAH - Hakim, Lukman; Sugiyanto, Eko (Prosiding University Research Colloquium, 2020)
The objectives of this study are: (1) To identify the causes of organizational changes that occur in the Sragen Masaran Batik industry. (2) Identifying the impact of organizational change in the Sragen Masaran Batik industry. (3) Analyzing the stages of organizational change that occur in the Sragen Masaran Batik industry. This study uses a descriptive method with a case study approach (Case Studies). Case studies are in-depth studies of individuals, one group, one organization, one program of activities, and so on within a certain time.The results of the study concluded that the causes of organizational change: (1) adjustment factors to the environment, (2) technological development, (3) government encouragement to improve the effectiveness of the industry, (4) changes in regulations or new systems in organizations, (5) changes in consumer tastes, (6) demands for organizational and employment changes. The impact of changes include: (1) changes in work procedures, quality and quantity of labor, (2) changes in decision making techniques at the leadership, (3) internal conditions in a conducive organization, (4) development goals and industrial strategies become more focus, (5) occurrence of work evaluation or improvement of industrial activities. Stages of change include: (1) conducting an assessment, (2) conducting an identification, (3) setting changes, (4) determining the strategy, (5) conducting an evaluation.